The Effect of Institutional Ownership, Family Ownership, and Thin Capitalization on Tax Avoidance - Tarmizi, Achmad; Hikmah Perkasa, Didin; Meliantari, Dian; Annisa Wahdiawati, Siti (KnE Social Sciences, 2023)
Taxpaying companies in Indonesia aim to maximize profit to increase the company’s shares value so that more investors are interested in investing in the company. This practice causes companies to try to pay taxes to a minimum by carrying out tax management without violating tax laws. This study examines and analyzes the effect of institutional ownership, family ownership, and thin capitalization on tax avoidance. Data used were from the manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021, using a purposive sampling technique. In the sample of this study, 6 companies met the criteria. This research uses the panel data regression analysis method which is a combination of time series and cross data to get more informative data. The table of the coefficient regression test result shows that the significant value for Institutional Ownership is 0.0295, <0.05 (alpha 5%) with a positive beta value in accordance with the hypothesis proposed in this study. Therefore, it can be stated that institutional ownership has a significant positive effect on tax avoidance at the 95% confidence level. The significant value for family ownership is 0.2213, >0.05 (alpha 5%) with a negative beta value and is not in accordance with the hypothesis proposed in this study. So, it can be stated that family ownership has no effect on avoidance. And, the significant value for thin capitalization is 0.0103, <0.05 (alpha 5%) with a positive beta value in accordance with the hypothesis proposed in this study. So, it can be stated that thin Capitalization has a significant positive effect on tax avoidance at the 95% confidence level. The F-statistic test was used to measure the accuracy of the sample regression function in estimating the actual value (goodness of fit). The F-test analyzes whether the independent variables are able to explain the dependent variable well or whether the model used is fit or not. The F-test in this study uses a significance level of 5%. From the table, it is known that the significant value is 0.005389 <0.05, which means that institutional ownership, family ownership, and thin capitalization simultaneously affect the dependent variable tax avoidance. Keywords: tax avoidance, institutional ownership, family ownership, thin capitalization